2017
DOI: 10.1177/1010428317714194
|View full text |Cite
|
Sign up to set email alerts
|

Neuron-specific enolase, histopathological types, and age as risk factors for bone metastases in lung cancer

Abstract: Lung cancer is a malignant tumor with high metastatic ability and bone is the most common site of distant metastasis of it. However, the independent risk factors for bone metastases of lung cancer remain largely to be elucidated. Here, we conducted a retrospective study to evaluate the correlation between clinical-pathological parameters, serum levels of neuron-specific enolase and CYFRA21-1, and bone metastases in lung cancer patients. The results revealed that patients with bone metastases were younger than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
0
11
1
Order By: Relevance
“…Genetic and proteomics-based biomarkers are two major types of biomarkers, which can be identified through tumor cells, urine, sputum, blood, or other body fluids [ 3 ]. Table 3 demonstrates numerous lung cancer markers [ 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 ].…”
Section: Biomarkers For Lung Cancer Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic and proteomics-based biomarkers are two major types of biomarkers, which can be identified through tumor cells, urine, sputum, blood, or other body fluids [ 3 ]. Table 3 demonstrates numerous lung cancer markers [ 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 ].…”
Section: Biomarkers For Lung Cancer Detectionmentioning
confidence: 99%
“…Many types of proteomic biomarkers have been investigated for lung cancer detection, including Annexin II [ 122 ], APOA1 [ 123 ], carcinoembryonic antigen (CEA) [ 124 ], carbohydrate antigen 125 (CA125) [ 125 ], carbohydrate antigen 19-9 (CA19-9) [ 126 ], cytokeratin fragment 21-1 (CYFRA21-1) [ 127 ], CD59 glycoprotein [ 128 ], transthyretin (TTR) [ 129 ], GM2 activator protein (GM2AP) [ 130 ], haptoglobin-R2 [ 131 ], Ig-free light chain [ 132 ], neuron-specific enolase (NSE) [ 133 ], nitrated ceruloplasmin [ 134 ], plasma kallikrein B1 [ 135 ], ProGRP [ 136 ], retinol binding protein (RBP) [ 137 ], squamous cell carcinoma (SCC) [ 138 ], vascular endothelial growth factor (VEGF) [ 139 ], TPA [ 140 ], and tumor M2-pyruvate kinase [ 141 ].…”
Section: Biomarkers For Lung Cancer Detectionmentioning
confidence: 99%
“…Single nucleotide polymorphism of TIPARP in Prostate has been proved to be related with cancer 26 . In 27 ENO2 is reported to be a risk factor for bone metastases in cancer. The TPD52L2 in GSE32603 encodes a member of the tumor protein D52-like family, and contributes to proliferation of cancer cells 28 .…”
Section: Resultsmentioning
confidence: 99%
“…The serum level of NSE in 28 patients with brain metastasis was significantly higher than that of 98 patients without metastasis (34.18 ± 28.48 vs. 13.87 ± 4.49 ng/ml, P <0.05). Zhou et al [114] also found that age, pathological type and serum NSE concentration of lung cancer patients are independent risk factors for bone metastasis. The NSE serum concentration of patients with bone lesions is significantly higher than those without bone metastasis (39.18 ± 62.18 vs. 29.16 ± 40.21 ng/ml, P =0.018) [114].…”
Section: γ-Enolase In Lung Cancermentioning
confidence: 99%
“…Zhou et al [114] also found that age, pathological type and serum NSE concentration of lung cancer patients are independent risk factors for bone metastasis. The NSE serum concentration of patients with bone lesions is significantly higher than those without bone metastasis (39.18 ± 62.18 vs. 29.16 ± 40.21 ng/ml, P =0.018) [114]. However, other studies have proposed that serum NSE level in NSCLC patients has no prognostic significance [115,116].…”
Section: γ-Enolase In Lung Cancermentioning
confidence: 99%